2022
DOI: 10.1109/access.2022.3192548
|View full text |Cite
|
Sign up to set email alerts
|

Design Methodology of Multiband Printed Antennas for Future Generations of Mobile Handsets

Abstract: The present paper introduces a design methodology to extend the operation of a microstrip patch antenna to operate efficiently at multiple higher-order resonances. This method depends on the geometrical modification of the antenna structure by adding well-designed inductively-loaded and capacitively-coupled elements to the primary patch so that it can efficiently radiate at the desired higher frequency bands. It is explained quantitatively how to use the geometrical parameters of the inductively and capacitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The most commonly used method to increase the bandwidth of such resonant microstrip patch antennas is to use a defected ground structure (DGS) that effectively increases the aperture size of the resonant cavity and, hence, increases the bandwidth. Also, a recently published work [7] has shown that loading the main radiator (patch) with capacitively coupled elements has the effect of enhancing the bandwidth and/or adding extra resonances to the radiating modes of the microstrip patch structures. It has been shown that using both techniques (partial removal of the ground plane and capacitive loading of the main patch with parasitic elements) [8] may result in adding more resonant frequency bands, and at the same time, improving the bandwidth of some of these radiating modes.…”
Section: Design Methodology and Geometry Of The Proposed Antennamentioning
confidence: 99%
“…The most commonly used method to increase the bandwidth of such resonant microstrip patch antennas is to use a defected ground structure (DGS) that effectively increases the aperture size of the resonant cavity and, hence, increases the bandwidth. Also, a recently published work [7] has shown that loading the main radiator (patch) with capacitively coupled elements has the effect of enhancing the bandwidth and/or adding extra resonances to the radiating modes of the microstrip patch structures. It has been shown that using both techniques (partial removal of the ground plane and capacitive loading of the main patch with parasitic elements) [8] may result in adding more resonant frequency bands, and at the same time, improving the bandwidth of some of these radiating modes.…”
Section: Design Methodology and Geometry Of The Proposed Antennamentioning
confidence: 99%
“…A resonator loaded patch antenna is designed in [10], a high performance air filled multi-mode resonant u slot antenna in [11], and a shared aperture antenna for base station application in [12] is proposed to obtain multiple bands. A design methodology is discussed to obtain multibands in printed antennas [13] and multiband monopole antenna with enhancement in bandwidth [14] for mobile handset application. In the above techniques, to obtain multiple bands much effort is needed in terms of design, feeding method, and optimization due to the sensitivity of parameters, and it is incapable to tune frequency bands independently.…”
Section: Introductionmentioning
confidence: 99%
“…In order to promote isolation, a decoupling structure is built that isolates the input of the radiating patches from the corresponding network arrangement in [8][9][10][11][12]. To increase the isolation between the patches, parasitic components are utilized in [13][14][15][16][17][18]. Using the literature mentioned above, it is necessary to create a MIMO antenna that operates on a multiband application with an ultra-wide bandwidth, improved TARC, and better cross correlation.…”
Section: Introduction Modern Antenna Technology Relies Heavily On Mul...mentioning
confidence: 99%